2021
DOI: 10.3389/fcvm.2021.757596
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Prognosis of HFimpEF Developed From Patients With Heart Failure With Reduced Ejection Fraction: Systematic Review and Meta-Analysis

Abstract: Background: Heart failure with improved ejection fraction (HFimpEF) is classified as a new type of heart failure, and its prevalence and prognosis are not consistent in previous studies. There is no systematic review and meta-analysis regarding the prevalence and prognosis of the HFimpEF.Method: A systematic search was performed in MEDLINE, EMBASE, and Cochrane Library from inception to May 22, 2021 (PROSPERO registration: CRD42021260422). Studies were included for analysis if the prognosis of mortality or hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 38 publications
4
27
0
Order By: Relevance
“…We found that 34.7% of our patients with non‐HFimpEF evolved to HFimpEF. In the meta‐analysis performed by He et al ., 37 the pooled prevalence of HFimpEF was only 22.64%, although it ranged from 10 to 52%.…”
Section: Discussionmentioning
confidence: 97%
“…We found that 34.7% of our patients with non‐HFimpEF evolved to HFimpEF. In the meta‐analysis performed by He et al ., 37 the pooled prevalence of HFimpEF was only 22.64%, although it ranged from 10 to 52%.…”
Section: Discussionmentioning
confidence: 97%
“…In a recent study by Li et al, HFimpEF, defined as an absolute increase in LVEF by 10% (regardless of baseline value), was found in 41.2% of cases [ 23 ]. In a recent meta-analysis by He et al performed on 9491 patients from nine studies, HFimpEF was present in 22.6% of patients [ 24 ]. All in all, the prevalence of HFimpEF varies from roughly 10 to 40% [ 9 ].…”
Section: Definition Of Hfimpefmentioning
confidence: 99%
“…A meta-analysis by Jorgensen et al also delivered evidence that a lower baseline LV end-diastolic diameter (LVEDD) is associated with a greater rate of HFimpEF [ 11 ]. Other studies identified a younger age, beta-blocker use, a valid indication for pulmonary vein isolation or CRT implantation, as well as chemotherapy cardiotoxicity among patients with malignant neoplasm, troponin levels within the reference value and elevated natriuretic peptides as independent predictors of HFimpEF [ 23 , 24 , 25 , 26 ]. In addition, convincing data suggests that baseline GLS accurately predicts future variations in LVEF, indicating that GLS is a more reliable and stable in-time parameter of systolic function [ 16 ].…”
Section: Definition Of Hfimpefmentioning
confidence: 99%
See 2 more Smart Citations